The reemergence of dengue virus in Sudan - Mujahed I. Mustafa; Abdelrafie M. Makhawi (Elsevier, 2023)
Dengue fever (DF) is a mosquito-transmitted arboviral disease caused by 1 of 4 closely related but antigenically distinct serotypes of dengue virus (DENV), DENV-1-4. The primary vector of DENV is Aedes aegypti and Aedes albopictus mosquitoes. Humans are the main carrier of the virus and the amplifying host with non-human primates plays a considerable role in sylvatic cycle. On November 8, 2022, an outbreak of dengue fever has killed at least five people in North Kordofan State. On 23 Nov 2022, the Sudanese Ministry of Health reported 3326 cases of dengue fever across 8 Sudanese States; while 23 patients died from the fever. Sudan is witnessing its worst outbreak of dengue fever in over a decade, especially in North and South Kordofan and Red Sea State are hit hard. In this review, we will focus on the recent outbreak of dengue fever in many Sudanese states.